Near‐Field Thermal Profiling and 3D Anisotropic Thermal Analysis of Quantum Cascade Lasers. Issue 8 (9th December 2022) - Abbas, Farhat; Daunis, Trey; Pandey, Binay J.; Clark, Kevin; Lascola, Kevin; Dikmelik, Yamac; Robbins, Dennis; Hodges, Kimari L.; Roodenko, Katy; Gu, Qing
Abstract : The development of a scanning near‐field optical microscopy (SNOM) method with high temperature and spatial resolution to probe the thermal behavior of quantum cascade lasers (QCLs) is reported. Specifically, thermal profiling of InGaAs/InAlAs/InP buried heterostructure (BH) mounted epi‐layer side down QCLs is performed. The findings are verified by 3D anisotropic thermal analysis of QCLs with anisotropic thermal conductivities in the superlattice active region. Good agreement is observed between the simulated and the measured time constants. Within this design, various realistic device configurations, such as overhanging the laser chip on the submount and placing different dielectric coatings on the front facet, are considered. Analytical studies of the steady‐state thermal performance of QCL arrays compared to an isolated QCL are demonstrated for high‐power requirements with minimal thermal damage and future application in spectroscopic devices. Abstract : An infrared scanning near field optical microscopy (IR‐SNOM) apparatus with high temperature and spatial resolutions, in combination with 3D anisotropic thermal simulations, is used to profile the thermal behavior of mid‐IR InGaAs/InAlAs/InP quantum cascade lasers with anisotropic thermal conductivities in the superlattice active region. Realistic device configurations, choices of dielectric coating, and arrayed device performance are also studied.